Human immunodeficiency virus-1 uses the mannose-6-phosphate receptor to cross the blood-brain barrier. - Shinya Dohgu; Jan S Ryerse; Sandra M Robinson; William A Banks (PLoS ONE, 2012)
HIV-1 circulates both as free virus and within immune cells, with the level of free virus being predictive of clinical course. Both forms of HIV-1 cross the blood-brain barrier (BBB) and much progress has been made in understanding the mechanisms by which infected immune cells cross the blood-brain barrier BBB. How HIV-1 as free virus crosses the BBB is less clear as brain endothelial cells are CD4 and galactosylceramide negative. Here, we found that HIV-1 can use the mannose-6 phosphate receptor (M6PR) to cross the BBB. Brain perfusion studies showed that HIV-1 crossed the BBB of all brain regions consistent with the uniform distribution of M6PR. Ultrastructural studies showed HIV-1 crossed by a transcytotic pathway consistent with transport by M6PR. An in vitro model of the BBB was used to show that transport of HIV-1 was inhibited by mannose, mannan, and mannose-6 phosphate and that enzymatic removal of high mannose oligosaccharide residues from HIV-1 reduced transport. Wheatgerm agglutinin and protamine sulfate, substances known to greatly increase transcytosis of HIV-1 across the BBB in vivo, were shown to be active in the in vitro model and to act through a mannose-dependent mechanism. Transport was also cAMP and calcium-dependent, the latter suggesting that the cation-dependent member of the M6PR family mediates HIV-1 transport across the BBB. We conclude that M6PR is an important receptor used by HIV-1 to cross the BBB.